Double-hit and triple-hit lymphomas arising from follicular lymphoma following acquisition of MYC: report of two cases and literature review - Xu, Xiaoxiao (e-Century Publishing Corporation, 2013)
Double-hit or triple-hit B-cell lymphomas (DHL and THL) are rare subtype lymphomas usually associated with poor prognosis. It is defined by two or three recurrent chromosome translocations; MYC/8q24 loci, usually in combination with the t (14; 18) (q32; q21) bcl-2 gene or/and BCL6/3q27 chromosomal translocation. DHL was often observed both in de-novo diffuse large B cell lymphomas (DLBCL). It is otherwise unclassifiable, showing features intermediate that of large B-cell lymphoma and Burkitt lymphoma. Here, we present two follicular lymphoma patients; one transformed to THL, another transformed to DHL. Both cases revealed aggressive clinical courses with poor prognosis and associated with acquisition of c-Myc gene (MYC) and central nervous system (CNS) involvement. We reviewed the related literature, correlated the immunophenotype and clinical manifestations such as response to therapy and prognosis. Although the incidence of DHT and THL is low, cytogenetic and FISH analyses should be included when B-cell lymphoma patients experience relapse or refractory course of disease. We concluded that c-Myc may contribute to aggressive transformation, and more mechanism-based therapy should be explored.